[The Theory of Relative Shares]: Reply - Gallaway, Lowell E. (Quarterly Journal of Economics, 1965)
Journal Article The Theory of Relative Shares: Reply Get access Lowell E. Gallaway Lowell E. Gallaway Wharton School of Finance and Commerce, University of Pennsylvania Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 79, Issue 4, November 1965, Pages 676–679, https://doi.org/10.2307/1880662 Published: 01 November 1965